الاجتهاد بتحقيق المناط في المعاملات المالية المعاصرة في ضوء مقاصد الشريعة - بدادي, بوكة (University of Eloued جامعة الوادي, 2021)
يقدم هذا البحث دراسة تأصيلية لأحد أبرز أدوات الاجتهاد التنزيلي، لتطبيقها على المعاملات المالية المعاصرة من خلال مجامع الفتوى والهيئات المالية الإسلامية، وذلك عن طريق تحقيق المناط وفق مقاصد الشريعة. وتكمن مشكلة الدراسة التي يعالجها هذا البحث في: مدى إعمال تحقيق المناط في مجال المعاملات المالية المعاصرة؟ وما الضوابط المعتبرة في ذلك؟ وهل لمقاصد الشريعة أثر في هذه الضوابط؟ وقد اتبعت الباحثة المنهج الاستقرائي والتحليلي، وكذا المنهج الوصفي والاستدلالي، وبموجبه تم تقسيم البحث إلى ثلاثة فصول ومقدمة وخاتمة. ومن أهم النتائج التي توصل إليها البحث هي أن: تحقيق المناط هو الاجتهاد في تعيين محل مناسب لتنزيل الحكم الشرعي، وبالتالي فهو من المناهج الشرعية التي لها الأثر البالغ في تحقيق مقاصد الشارع من الأحكام. summary This research presents an original study of one of the most prominent tools of lowerlevel ijtihad, to be applied to contemporary financial transactions through fatwa councils and Islamic financial bodies, by achieving the mandate according to the purposes of Sharia. The problem of the study dealt with in this research lies in: The extent to which the realization of the mandate is implemented in the field of contemporary financial transactions? What are the controls considered in that? Do the purposes of Sharia impact on these controls? The researcher followed the inductive and analytical method, as well as the descriptive and inferential method, according to which the research was divided into three chapters, an introduction and a conclusion. Among the most important findings of the research are: The realization of the mandate is the diligence in determining an appropriate place to download the legal ruling, and therefore it is one of the legal methods that have a great impact in achieving the purposes of the law in terms of rulings.
أطروحة دكتوراه. تخصص الفقه وأصوله. معهد العلوم الإسلامية. جامعة الوادي
Keywords: تحقيق المناط، المعاملات المالية المعاصرة، مقاصد الشريعة; Realization of Manat, Contemporary Financial Transactions, Maqasid al-Shariah